Insiders Researching the Constraints (Rigidities) and Flexibilities of their Academic Culture. The University of Barcelona Case - Sancho-Gil, Juana M.; Hernández-Hernández, Fernando (Acta Paedagogica Vilnensia, 2017)
This paper discusses how the search for more meaningful ways of teaching and learning in higher education has led us to considering contemporary notions of knowledge and learning related to youth values, such as DIY culture (Spencer 2005). In the European project DIYLab, we have studied what happens when a group of insiders explore their own academic culture and the connections this approach has with the current reflexion on the limits and possibilities of ethnographic research in education. The analyzed evidence shows the rigidity of institutional times and spaces, the fragmented notion of knowledge and some institutional fissures through which a refreshing, demanding and challenging culture of teaching and learning could be inoculated.